Work Engagement & Effective Factors Among Nurses In General Teaching Hospital Of Shiraz University Of Medical Sciences - Sanaz Sohrabi Zadeh; Ariyan Gholipour; Zahra Kavosi; Ali Keshtkaran; Zahra Sharafi (Tehran University of Medical Sciences, 2012)
Background and Aim: Work engagement is defined as a positive, fulfilling, work-related state of mind that is characterized by vigor, dedication, and absorption. Since the quality of care delivery to patients depends on nurse's practices, the objective of this study was to determine work engagement & its effective factors among nurses of general hospitals of Shiraz University of Medical Sciences. Materials and Methods: This cross sectional study was performed among 273 in-patient nurses of Namazi and Faghihi hospitals using 2 stages of sampling. Our questionnaire was validated by experts opinions and Cronbach's alpha index (86%). Descriptive statistics and correlation tests were used for the analysis of data by SPSS. Results: According to the results obtained, mean work engagement was 58.95 ± 10.51 and there was a significant correlation between work engagement and organizational - supervisor support, organizational justice, job characteristics, reward & recognition, organizational citizenship behavior, organizational commitment, job satisfaction, turnover( p<0.05). The relationship between work engagement and reward was the strongest(r=0.512). Conclusion: The results imply the importance of work engagement and its related factors. Nurses are one of the biggest health system groups, and their burnout disadvantages hospitals and community. Thus, work engagement should be noticed in all policy-making related to nurses.